Two pulses of Mesoproterozoic intra-plate magmatism in the heart of the Palaeoproterozoic Ubendian Domain of northern Malawi - (:unkn) unknown (My University, 2023)
Two Mesoproterozoic anorogenic igneous events are recorded in the Palaeoproterozoic Ubendian Domain in northern Malawi. The oldest is represented by the Mwakikome orthogneiss, a small peraluminous, sub-alkaline and ferroan syenogranite that has a U–Pb zircon emplacement age of 1411 ± 3 Ma, an initial εNd of −4.5 and a Nd TDM2 model age of 2.27 Ga. These data are interpreted to suggest that the Mwakikome intrusion was derived mainly from the melting of the adjacent Palaeoproterozoic country rocks during Kibaran-aged extension. The second anorogenic igneous event is defined by the more widespread Mwenga Suite, a series of small (<100 km2) NW-SE oriented and elongated plutons that occur in a narrow belt in the north of the Ubendian Domain. Seven samples from different intrusions gave U–Pb zircon emplacement ages between ∼1150 and 1110 Ma. The Mwenga Suite is comprised of rocks that are also ferroan, potassic and sub-alkaline in composition and shows a range of major element compositions from monzogranite to alkali-feldspar granite. Nd isotopic data from one sample yielded an initial εNd of −2.2 and a Nd TDM2 model age of 1.88 Ga, suggesting that the suite was also largely derived from melting of the Ubendian host rocks, but with some additions from an enriched mantle source. Both the Mwakikome and Mwenga rocks are characterised by high concentrations of Zr, Hf, Nb, Ta, Y and REE and high Ga/Al, imparting a within-plate, A-type, trace element signature. The rocks have no direct temporal correlatives beyond northern Malawi and SW Tanzania and appear unique to this region. They do, however, build on a theme of long-lived Mesoproterozoic (∼1400–1100 Ma) intra-plate extension, basin formation, and bimodal A-type magmatism that is better established in areas of central Africa located over 500 km NW of the study area.
Keywords: African Research